Chemical composition, antioxidant, antimicrobial and antiproliferative activity of Laureliopsis philippiana essential oil of Chile, study in vitro and in silico - Bruna, Flavia Alejandra (2022)
Chilean Laureliopsis philippiana has been used in traditional medicine by the Mapuche and their ancestors. To evaluate its pharmacological activity, Laureliopsis philippiana leaf essential oil extract (LP_EO) was chemically and biologically characterized in the present study. In vitro antioxidant potential was analyzed, and antitumor activity was evaluated in non-tumor and tumor cell culture lines. Caenorhabditis elegans was used as a model for evaluating toxicity, and the chemical composition of the essential oil was analyzed using gas chromatography–mass spectrometry. The oil contains six major monoterpenes: eucalyptol (27.7 %), linalool (27.6 %), isozaphrol (19.5 %), isohomogenol (12.6 %), α-terpineol (7.7 %), and eudesmol (4.8 %). Based on quantum mechanical calculations, isosafrole and isohomogenol conferred in vitro antioxidant and antimicrobial activity to LP_EO. In addition, LP_EO showed antimicrobial activity against clinical Helicobacter pylori isolates (MIC 64 and MBC > 128 μg·mL−1), Staphylococcus aureus (MIC 32 and MBC > 64 μg·mL−1), Escherichia coli (MIC 8 and MBC 16 μg·mL−1) and Candida albicans (MIC 64 and > 128 μg·mL−1). LP_EO could selectively inhibit the proliferation of epithelial tumor cell lines but showed low toxicity against Caenorhabditis elegans (0.39 to 1.56 μg·mL−1). Therefore, LP_EO may be used as a source of bioactive compounds in novel pharmacological treatments for veterinary and human application, cosmetics, or sanitation.